descompunand in factori x4 - x2 + 1 se obtine?
Răspunsuri la întrebare
Răspuns de
3
x⁴ -x²+1= x⁴ +2x² +1 -3x² =( x² + 1)² - 3 x² = (x² +1)² - ( √3x)²=
= ( x² +√3x +1) ( x² - √3x +1)
= ( x² +√3x +1) ( x² - √3x +1)
alinispas95:
mersi mult!
Răspuns de
0
x⁴ -x²+1= x⁴ +2x² +1 -3x² =( x² + 1)² - 3 x² = (x² +1)² - ( √3x)²
Alte întrebări interesante
Matematică,
9 ani în urmă
Limba română,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Engleza,
10 ani în urmă
Limba română,
10 ani în urmă